PERBANDINGAN KARAKTERISTIK ASHPALT CONCRETE WEARING COURSE MODIFIKASI PG 70 DAN ASPAL PENETRASI 60/70 DENGAN BAHAN TAMBAH ANTI STRIPPING AGENT - Muhammad Agus Kurniawan (Pondasi, 2025)
Road pavement plays a crucial role in supporting connectivity and economic development, with the wearing course acting as the primary layer subdjected to traffic loads and environmental exposure. In Indonesia, commonly used asphalt types include penetration grade 60/70 and PG 70 modified asphalt, the latter offering superior resistance to deformation and cracking. To mitigate moisture-induced stripping, anti stripping agents (ASA) such as hydrated lime are applied to enhance adhesion and improve mixture durabilitu. This study aoims to analyze the characteristics of Asphalt Concrete Wearing Course (AC-WC) mixtures utilizing both asphalt types, and to evaluate the influence of ASA on performance enhancement, in order to recommend optimal materials for pavement applications. The research methodology involves laboratory-based experimental testing of AC-WC mixtures prepared with the two asphalt types, both with and without the addition of hydrated lime as an ASA. The evaluation focuses on volumetric properties (VIM,VMA,VFB,stability,flow,and Marshall Quotient (MQ) to determine the most suitable materials for pavement applications. The findings indicate that PG 70 modified asphalt yields higher stability and MQ values than penetration grade 60/70 asphalt, and demonstrates better moisture resistance. Moreover, ASA addition significantly enhances the adhesive bond and stripping resistance in both asphalt types. Based on the rest result, AC-WC mixtures incorporating PG 70 asphalt and ASA are recommended for road pavement in tropical regions with high traffic volumes